2012
DOI: 10.1242/dev.073924
|View full text |Cite
|
Sign up to set email alerts
|

Gβγ signaling controls the polarization of zebrafish primordial germ cells by regulating Rac activity

Abstract: SUMMARYDuring development, primordial germ cells (PGCs) migrate from the sites of their specification towards the region in which the future gonad develops. This cell migration requires polarization of PGCs and their responsiveness to external guidance cues. In zebrafish, the directed migration and polarization of PGCs are regulated independently, by the chemokine Cxcl12a and the Rho GTPase Rac1, respectively. However, the upstream signals controlling Rac activity in this context have not yet been identified. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 25 publications
1
43
0
Order By: Relevance
“…We previously identified 5 Gβ isoforms (9 members, of which all except Gβ2 are duplicated) in the zebrafish genome. Among the encoding genes, those for the Gβ1 and Gβ4 isoforms ( gnb1a, gnb1b , gnb4a, gnb4b ) are maternally and ubiquitously expressed during gastrulation (Xu et al, 2012). In this study, we found that their expression continues throughout the embryo from 30–48 hours post fertilization (hpf), particularly in the anterior region of embryo (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously identified 5 Gβ isoforms (9 members, of which all except Gβ2 are duplicated) in the zebrafish genome. Among the encoding genes, those for the Gβ1 and Gβ4 isoforms ( gnb1a, gnb1b , gnb4a, gnb4b ) are maternally and ubiquitously expressed during gastrulation (Xu et al, 2012). In this study, we found that their expression continues throughout the embryo from 30–48 hours post fertilization (hpf), particularly in the anterior region of embryo (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the functions of Gβ1 and Gβ4 during pLLP migration, we inhibited their expression using previously validated antisense morpholino oligonucleotides (MOs, in this case MO1) (Xu et al, 2012). Western blotting using an antibody that specifically recognizes zebrafish Gβ1 (both the Gβ1a and Gβ1b isoforms) confirmed that injection of MOs targeting both gnb1a and gnb1b ( gnb1a/b MO1) led to 81% reduction of the Gβ1 expression in 24-hpf embryos (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has found that a defect in Gbg signaling leads to alterations in cell migration, which requires reorganization of the actin-cytoskeleton network (Peracino et al, 1998;Hwang et al, 2005;Xu et al, 2012). Upon GPCR activation by chemokines, G protein heterotrimers are believed to dissociate and modulate many signaling pathways that control cell migration.…”
Section: A Gbg Effects On Cell Division and The Cytoskeletonmentioning
confidence: 99%
“…Biosensor imaging has been applied to classic models of embryonic development less frequently than whole animal physiology, with only a handful of successes reported in zebrafish (Andrews et al, 2016; Muto et al, 2011; Xu et al, 2012; Zhao et al, 2015), Drosophila (Markova et al, 2015), and C. elegans (Kelley et al, 2015; Vuong-Brender et al, 2018). Consequently, less is known about protein activities during development outside of gene expression.…”
Section: Introductionmentioning
confidence: 99%